(untitled) (Global Journal of Computer Science and Technology, 2013)
The paper investigates the intensity of (Social Networking Sites) SNSs use among the students of Jordanian universities. Four universities were involved in this study, while 727 undergraduate students respond to a questionnaire that measured their intensity of SNSs use. To answer research questions, the researchers used descriptive statistics, ANCOVA, Chi-Square, and T-test. The data analyses revealed significant differences among students’ uses of SNSs. The variables consisted of university, faculty, gender, and year level. The study recommendation was the focus on integrating SNSs within learning management systems.